PACAP/PAC1 regulation in cystitis rats: induction of bladder inflammation cascade leading to bladder dysfunction - Ke, Hanwei; Zhu, Lin; Zhang, Weiyu; Wang, Huanrui; Ding, Zehua; Su, Dongyu; Wang, Qi; Xu, Kexin (Frontiers in Immunology, 2024)
IntroductionInterstitial Cystitis/Bladder Pain Syndrome (IC/BPS) is a chronic and debilitating condition marked by bladder pain, urinary urgency, and frequency. The pathophysiology of IC/BPS remains poorly understood, with limited therapeutic options available. The role of Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) and its receptor PAC1 in IC/BPS has not been thoroughly investigated, despite their potential involvement in inflammation and sensory dysfunction. This study aims to examine the expression and functional role of the PACAP/PAC1 signaling pathway in the pathogenesis of IC/BPS.MethodsBladder tissue samples from IC/BPS patients and a rat model of cystitis were analyzed to evaluate PACAP and PAC1 expression. Transcriptomic analysis, immunohistochemistry, and bladder function assays were employed to assess the correlation between PACAP/PAC1 activation, bladder inflammation, and sensory dysfunction. Additionally, modulation of the PACAP/PAC1 pathway was tested in rats to determine its effects on bladder inflammation and function.ResultsOur results demonstrate significant upregulation of PACAP and PAC1 in both human bladder tissues from IC/BPS patients and in the rat cystitis model. This upregulation was associated with increased bladder inflammation and sensory dysfunction. Intervention with PACAP/PAC1 pathway modulation in rats resulted in a marked reduction in bladder inflammation and improvement in bladder function, suggesting the pathway’s pivotal role in disease progression.DiscussionThe findings provide compelling evidence that the PACAP/PAC1 pathway is involved in the inflammatory and sensory changes observed in IC/BPS. By targeting this signaling pathway, we may offer a novel therapeutic approach to mitigate the symptoms of IC/BPS. This study enhances our understanding of the molecular mechanisms driving IC/BPS and opens avenues for the development of targeted treatments.